Analisis Penerapan dan Efektifitas e-Faktur dalam Pelaporan SPT Masa PPN (Studi Kasus di PT. Tunas Surya Sentausa) - Selvia Febrianti; Erry Andhaniwati (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Tax is a citizen's contribution to the state treasury which is based on law (enforceable), without special consideration (compensation), verified directly and used to finance state expenditure. e-Invoice was developed by the Directorate General of Taxes to facilitate the creation of digital tax invoices by PKP and reduce the occurrence of tax invoice forgery and the creation of fictitious tax invoices that have an impact on the VAT payable. The implementation of digital tax invoices is processed in the Regulation of the Director General of Taxes PER-16/PJ/2014 which will be implemented slowly starting on July 1, 2014, July 1, 2015, and finally July 1, 2016. The purpose of this study was to determine the implementation of electronic invoice-based SPT reporting and how effective it is in reporting VAT Periodic SPT at PT. Tunas Surya Sentausa. The method used is qualitative by utilizing primary data collected from PT. Tunas Surya Sentausa. The results show that the level of e-invoice implementation is in accordance with DJP regulations and the existence of this e-invoice application is very effective in processing electronic invoices.